Analisis dan Penerapan Aplikasi Sistem Komunikasi Sekolah SMPN 1 Kradenan Berbasis Web dan SMS Gateway - FAHRURROZI, FAISAL; , Gunawan Ariyanto,ST. M. Compt Sc., Ph.D (2016)
Given the rapid advances in technology that has penetrated into all areas as well as the pattern of Indonesian society which is more advanced, it is certain that everyone is now utilize cellular technology both GSM and CDMA as well as Internet media that in fact this can be directed to an added value in the context of the advancementofeducation. Similarly, the SMS service as one of the mobile service of the most popular and most in demand today because its use is relatively easy and very low cost can be utilized parents monitor student attendance in school and payment of buildings in SMPN 1 Kradenan, schools could menfaatkan to convey academic information via sms broadcasting feature to a mobile phone respective parents with sms gateway.